Critical Review: Strategic Supply and Transportation Planning of a Supply Chain for Agricultural Biomass to Hydrogen and Syngas - Bhenu Artha; Ascasaputra Aditya; Antonius Satria Hadi; Bahri Bahri; Niken Permata Sari; Utami Tunjung Sari; Cahya Purnama Asri; Rhamadinna Fatimah (Program Studi Teknik Industri, Fakultas Sains dan Teknologi, Universitas Widya Mataram, 2026)
In the evolving landscape of renewable energy, the management of agricultural biomass supply chains has emerged as a critical success factor for sustainable fuel production, this article presents a critical review of the research conducted by Nugroho and Zhu (2024) regarding the strategic supply and transportation planning of an agricultural biomass supply chain for hydrogen and syngas production. The primary study addresses a significant gap in renewable energy management by proposing a bi-level optimization framework that utilizes Stackelberg game concepts to model non-cooperative interactions between biofuel producers and biomass suppliers. The review identifies several methodological strengths, including the integration of process-level material balances with supply chain decisions and the use of mixed-integer nonlinear programming (MINLP) to handle realistic cost components like holding and production costs. However, the analysis also highlights critical limitations, such as restrictive behavioral assumptions regarding risk neutrality and perfect information, which may not reflect real-world opportunistic conduct. Furthermore, the generalizability of the findings is constrained by a narrow focus on an Indonesian case study and a dual-sourcing strategy that may face scalability issues in larger regional networks. Ultimately, while the reviewed work is deemed an incremental rather than landmark contribution, it offers valuable structured recommendations for practitioners and project developers building biomass supply chains in agricultural regions.